Psychometric Properties of the Primary Care PTSD Screen for DSM-5: Findings From Family Members of Chinese Healthcare Workers During the Outbreak of COVID-19 - Cheng, Peng; Jasinski, Nicholas; Zheng, Wanhong; Yadava, Aradhita; Wang, Lirong; Li, Lingjiang; Xu, Lizhi; Zhou, Ying; Zhang, Li; Li, WeiHui (Frontiers in Psychiatry, 2021)
Background: Minimal research has examined utility of PC-PTSD-5 in family members of frontline medical workers. The aims of our study were to develop and elucidate the psychometric properties of the Chinese version of the PC-PTSD-5 and to determine its usefulness in screening for possible PTSD in relatives of Chinese healthcare workers during the COVID-19. Methods: We conducted a cross-sectional research in the relatives of medical staffs working in a general hospital during the COVID-19. Descriptive analysis was used to characterize demographic information of family members to find factors associated with PTSD symptoms. For reliability test, the internal consistency of PC-PTSD-5 was accessed using Cronbach's alpha coefficient. The validity test was assessed by Pearson's correlation between scales. A receiver operating characteristic (ROC) curve was used to evaluate the optimal cutoff score with the maximum Youden Index in this study. Results: The result of demographic information indicated that gender and the type of work undertaken by medical staff in the family have a potential impact on the PTSD symptoms of medical staff’s family members. Cronbach's alpha coefficient of PC-PTSD-5 was 0.83, indicating the high reliability. Good validity was also proved by Pearson coefficient. By calculating the Youden index, a cutoff score of 2 was found to be optimal in our study, with sensitivity of 80.74% and specificity of 88.43%. Conclusions: Our study has demonstrated the robust psychometric strengths of the PC-PTSD-5, introducing a reliable tool for screening PTSD among vulnerable and neglected families of these medical workers.